Analysis of oxidative stress expressed by urinary level of biopyrrins and 8‐hydroxydeoxyguanosine in patients with chronic schizophrenia. Issue 11 (14th July 2015) - Miyaoka, Tsuyoshi; Ieda, Masa; Hashioka, Sadayuki; Wake, Rei; Furuya, Motohide; Liaury, Kristian; Hayashida, Maiko; Tsuchie, Keiko; Arauchi, Ryosuke; Araki, Tomoko; Shioji, Izuru; Ezoe, Satoko; et al.
Abstract : Aims: Previous studies have supported the claim that psychological stress induces the production of reactive oxygen species. Several authors have suggested that patients with psychiatric disorders show high levels of oxidative stress markers. We examined different oxidative stress markers in patients with chronic schizophrenia. Methods: This study included 29 patients with chronic schizophrenia and 30 healthy volunteers. The concentration of urinary biopyrrins and 8‐hydroxydeoxyguanosine (8‐OHdG), as measured by enzyme‐linked immunosorbent assay, were normalized to the urinary concentration of creatinine. Psychiatric symptoms were assessed by the administration of the Brief Psychiatric Rating Scale (BPRS). Results: The concentration of biopyrrins in patients with chronic schizophrenia was significantly higher when compared with healthy volunteers. The correlation between biopyrrin level and the duration of illness was highly significant. There were no significant differences in the levels of urinary 8‐OHdG between the two groups. In schizophrenic patients, the level of urinary biopyrrins showed correlations with BPRS scores, while the level of urinary 8‐OHdG did not show correlations with BPRS. Conclusions: Urinary biopyrrins are increased in patients with chronic schizophrenia while urinary 8‐OHdG is not increased. These findings suggest that patients with chronic schizophrenia are under the condition of certain oxidative stresses.